ANALISA KANDUNGAN NATRIUM BENZOAT PADA BUAH KEMASAN KALENG YANG BEREDAR DI KOTA MEDAN TAHUN 2013 - nazar uddin; evi naria; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Content of sodium benzoate on canned fruit in the medan city 2013. Canned fruit is the fruit packaging in a sealed tin container so that the bodies of destroyers and air can not enter into it. In the canned fruit does not reveal any information on the use of sodium benzoate as a preservative canned fruit last for years. The purpose of this study was to determine the general idea of ​​whether or not the preservative sodium benzoate and abortion levels in fruit cans in circulation in the city of Medan in 2013. This research is a descriptive survey study that analyzes the content of sodium benzoate on canned fruit with a sample of 10 samples consisting of 5 samples of fruit and 5 samples of canned fruit syrup obtained from several supermarkets in the city of Medan. Samples were then taken for examination in the Central Health Laboratory in North Sumatra province. The results of this research indicated shows the content of the preservative sodium benzoate in 10 samples still meet the health requirements for public consumption. Highest levels of sodium benzoate found in klenkeng fruit syrup samples were coded samples B2 0,608 g/kg material and owest levels of sodium benzoate found in rambutan fruit samples were coded samples C1 0,037 g/kg material. Conclusion, it is suggested to the manufacturer should include all types of preservatives used in canned fruits and consumers should be more selective in choosing food that will be consumed especially food preservatives. Keywords: preservative sodium benzoate, canned fruit